Implementación de la carrera académica de turismo de aventura en la Universidad San Francisco de Quito - Proaño Iturralde, Felipe José (2015)
Ecuador is a country perfectly fit to develop adventure tourism due to its re-sources, small territory and short distances. Adventure tourism is growing world-wide and Ecuador has a touristic industry ready to be developed. Universidad San Francisco de Quito is the pioneer institution in academic education in Ecuador and has the means and resources to offer a study program in Adventure Tourism to form professionals in this area and develop tourism in Ecuador. Through a precise research and analysis, the opportunity and design of an Adventure Tourism career in Universidad San Francisco de Quito is proposed.